Respostas
respondido por:
0
Encontrar o termo geral da PA:
an = a1 + ( n -1) . r
an = 3 + ( n -1) . 3
an = 3 + 3n - 3
an = 3n
===
an = 3n
a1 = 3.1
a1 = 3
a2 = 3.2
a2 = 6
a3 = 3.3
a3 = 9
a4 = 3.4
a4 = 12
a5 = 3.5
a5 = 15
PA = (3, 6, 9, 12, 15 )
an = a1 + ( n -1) . r
an = 3 + ( n -1) . 3
an = 3 + 3n - 3
an = 3n
===
an = 3n
a1 = 3.1
a1 = 3
a2 = 3.2
a2 = 6
a3 = 3.3
a3 = 9
a4 = 3.4
a4 = 12
a5 = 3.5
a5 = 15
PA = (3, 6, 9, 12, 15 )
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás